SHARĪ’AH SEBAGAI HUKUM TUHAN DAN POSISINYA DIANTARA ALIRAN FILSAFAT HUKUM - Khozainul Ulum (LPPM Institut Agama Islam Al-Hikmah Tuban, 2012)
In the understanding of Islamic law, there are two dimensions: first, ilāhiyah dimension of Islamic law, because he believed the teachings that come from God (Allah). Secondly, Islamic law insāniyah dimension. In this dimension, Islamic law is a human attempt seriously to understand the teachings of which was considered sacred by the two approaches, namely the approach of language (linguistic/lughawi) and maqasid approach. Islamic law, the law of God because it comes from khitāb Allāh recorded in al-Quran and Sunnah, from al-Quran and Sunnah is, the scholars to understand and then produces the laws of the various methodological tools to stand on